2021
DOI: 10.3390/ijerph18116016
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Mandibular Third Molar Impaction and Assessment of Surgery Difficulty: A Retrospective Study of Radiographs in East Baltic Population

Abstract: Classifications of impacted teeth allow defining the type and degree of retention, as well as assessing the degree of difficulty of the procedure. The aim of this study was to conduct retrospective analysis of the degree of retention and difficulty in the surgical removal of impacted mandibular third molars in the clinical material of the Department of Oral Surgery in 2013–2018. This study included 1585 dental panoramic radiographs of patients of the Department of Oral Surgery, who reported in 2013–2018, in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 27 publications
3
28
1
2
Order By: Relevance
“…Our study showed a more significant variation in the spatial position of teeth scheduled for extraction than in the above investigators. In addition, root anatomy, which is sometimes independent of the spatial position of the tooth, is an essential factor determining the difficulty of the procedure [51]. It should be noted that variations in the root structure of wisdom teeth often affect the anatomic scope of the surgical extraction procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a more significant variation in the spatial position of teeth scheduled for extraction than in the above investigators. In addition, root anatomy, which is sometimes independent of the spatial position of the tooth, is an essential factor determining the difficulty of the procedure [51]. It should be noted that variations in the root structure of wisdom teeth often affect the anatomic scope of the surgical extraction procedure.…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms can be observed particularly frequently as a consequence of surgical removal of mandibular third molars—a procedure considered to be the one of the most difficult and time-consuming among all oral surgery procedures. At the same time, it constitutes one of the most frequently performed procedures within this specialty [ 1 , 2 , 3 , 4 ]. The factors that determine the difficulty of the surgical procedure of avulsion of the third molar are depth and space available for removal of the impacted mandibular third molar, the angulation of the tooth, root spacing, size of the bone septum, presence or absence of a dilated tooth follicle, periodontal space, bone density, and the relation to the inferior alveolar nerve.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes the detailed results of the study sample. The spatial location of impacted third molars in the mandible was determined using Winter and Pell and Gregory's classifications [6]. The position of the impacted teeth is shown in Table 2.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Like any other surgery, it involves the risk of complications including tissue swelling, trismus, pain, infection, lip and tongue sensory deficits as well as damage to an adjacent tooth [3]. The age, gender of the patient, the degree of retention of the impacted tooth, and the operator's experience affect the appearance of complications associated with the surgical removal of an impacted mandibular third molar [4][5][6]. Complications prolong the postoperative recovery period and cause swelling, trismus, or inflammatory complications and may eventually lead to clinical changes in the mandibular second molar region [7].…”
Section: Introductionmentioning
confidence: 99%